EFFORTS TO IMPROVE STUDENT ACHIEVEMENT THROUGH THE DISCOVERY LEARNING MODEL - Khamdan; Artika, Juli (Jurnal Pendidikan Profesi Guru, 2025)
The Effect of Discovery Learning on Student Achievement in Al-Qur'an Hadith Studies. This research addresses the following issues. Does the Discovery Learning model affect the learning outcomes of Grade VIII students in the subject of Al-Qur’an Hadith at MTs NU Nurul Huda. To what extent do students master the material on Mad Silah, Mad Badal, Mad Tamkin, and Mad Farqi after implementing the Discovery Learning model. To examine the impact of the Discovery Learning model on student achievement in Al-Qur’an Hadith studies, particularly in the rules of Mad reading at MTs NU Nurul Huda Kudus for the academic year 2022/2023. To analyze the extent of students' learning progress after applying the Discovery Learning model in Grade VIII at MTs NU Nurul Huda Kudus. his study used action research conducted in two cycles. Each cycle consisted of four stages, Planning, Implementation and Observation, Reflection, Revision. The research subjects were Grade VIII students, and data were collected through formative tests and classroom observation sheets. The results showed a significant improvement in student learning outcomes, Pre-cycle 14%, Cycle I 42%, Cycle II 83%. the study concludes that the Discovery Learning method has a positive effect on students' learning motivation and significantly enhances their achievement in Al-Qur’an Hadith studies. This model can be used as an alternative learning approach to improve student engagement and understanding in religious studies.